Pengaruh Kepemilikan Manajerial, Kepemilikan Institusional dan Dewan Komisaris Independen terhadap Nilai Perusahaan - Yuliusman Yuliusman; Indra Lila Kusuma (ITB AAS INDONESIA, 2023)
The tittle of this research is the influence of managerial ownership, institutional ownership and independent commissioner board on the firm value of mining in Indonesia Stock Exchange period of 2014-2020. This research aimed to examine the influence of managerial ownership, institutional ownership and independent commissioner board on the firm value simultaneously and partially. The study used 24 mining company in Indonesia Stock Exchange in the period of 2014-2020 as a sampel. The sample was determined by using purposive sampling. Analysis of data using multiple regression analysis with Eviews 8. The result showed that partially managerial ownership, institutional ownership and independent commissioner board had effect on the firm value. Simultaneously that managerial ownership, institutional ownership and independent commissioner board had effect on the firm value.